Efficacy of sub - hypnotic dose of propofol or dexamethasone for attenuation of intrathecal morphin - induced post - operative nausea and vomiting in parturient under cesarean section - a randomized control trial - Hau, Nguyen Trung; Dung, Le Van; Hien, Nguyen Viet Quang; Quang, Nguyen Thanh; Nam, Nguyen Ich Hai; Loan, Nguyen Thi Thanh; Hang, Pham Thi Diem; Khoi, Le Viet Nguyen; Tuan, Bui Anh; Phu, Vo Hoang; và c.s. (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: Preventing nausea and vomiting in women undergoing post cesarean section played an important role in improving quality of care, enhanced patient satisfaction in breastfeeding and caring for the newborns.This study aimed to determine the incidence of postoperative nausea and vomiting among parturients receiving sub-hypnotic dose of propofol or dexamethasone as prophylaxis after cesarean section under intrathecal morphine to extend post-operative analgesia and the side effects of these drugs on patients. Methods: The study was conducted on 180 pregnant women with written informed consent.All pregnant women under spinal anesthesia were supplemented with intrathecal morphine for postoperative extended analgesia andeach recruited parturient was assigned to one of 3 groups using random allocation software. 60 parturients in each group were allocated to 0.5 mg/kg of propofol or 8 mg of dexamethasone (for post - operative nausea and vomiting prophylaxis) and NaCl 0.9% for the control group. Postoperative nausea and vomiting (PONV) incidence, heart rate, blood pressure, SpO2, respiratory rate, Richmond Agitation Sedation Scale (RASS) score and side effects of propofol and dexamethasone were recorded. Results: It was noted that the incidence of post-operative nauseasignificantly decreased in the propofol group (18,3%) or the dexamethasone group (20%) compared with the control group (51,7%) (P < 0.05).Similarly, post-operative vomiting was significantly reduced in the propofol group (6,7 %) or the dexamethasone group (8,3 %) compared with the control group (21,7%) (P < 0.05).There were no changes among parturients from the control group, propofol group, and the dexamethasone group regarding heart rate, blood pressure, SpO2, respiratory rate and RASS score. 11(18,3%) from the propofol group experienced pain. There were no side - effects related to dexamethasone. Conclusion: This study’s findings suggested that a sub- hypnotic dose of propofol could be as effective as dexamethasone in preventing PONV in parturient undergoing cesarean section under spinal anesthesia with intrathecal morphine to extend post-operative analgesia. There were no effects on vital signs, except for pain on propofol injection.